Delayed diagnosis of Hyperinsulinism Hyperammonemia Syndrome: A case report - Ngoc, Can Thi Bich; Khanh, Nguyen Ngoc (Tạp chí Nghiên cứu Y học, 2025)
Hyperinsulinism Hyperammonemia Syndrome (HI/HA syndrome) is an autosomal dominant disease caused by activating mutations in GLUD1, the gene responsible for encoding the mitochondrial enzyme glutamate dehydrogenase (GDH). This syndrome represents the second most common genetic form of congenital hyperinsulinism in infancy. Children with HI/HA syndrome typically experience hypoglycemic symptoms triggered by fasting or high-protein meals and persistently elevated ammonia levels. We report a case of HI/HA syndrome in a 7-month-old female who presented with cyanosis and hyperammonemia, along with an initial normal glucose level at the time of presentation. About one week after the child’s admission to the hospital, we discovered that hypoglycemia was the cause of her irritability. The hypoglycemic episode was found to occur coincidentally with hyperammonemia. The combination of clinical findings, biochemical markers, and genetic sequencing identifying a GLUD1 pathogenic variant facilitated the correct diagnosis of HI/HA syndrome. As demonstrated by this case, the diagnosis of HI/HA syndrome requires a thorough clinical evaluation, comprehensive biochemical analysis, and genetic testing. With the correct diagnosis, a patient with HI/HA syndrome can receive ongoing monitoring and care with the goal of preventing adverse neurologic sequelae. Hyperinsulinism Hyperammonemia Syndrome (HI/HA syndrome) is an autosomal dominant disease caused by activating mutations in GLUD1, the gene responsible for encoding the mitochondrial enzyme glutamate dehydrogenase (GDH). This syndrome represents the second most common genetic form of congenital hyperinsulinism in infancy. Children with HI/HA syndrome typically experience hypoglycemic symptoms triggered by fasting or high-protein meals and persistently elevated ammonia levels. We report a case of HI/HA syndrome in a 7-month-old female who presented cyanosis and hyperammonemia, along with an initial normal glucose level at the time of presentation. About one week after the child’s admission to the hospital, we discovered that hypoglycemia was the cause of her irritability. The hypoglycemic episode was found to occur coincidentally with hyperammonemia. The combination of clinical findings, biochemical markers, and genetic sequencing identifying a GLUD1 pathogenic variant facilitated the correct diagnosis of HI/HA syndrome. As demonstrated by this case, the diagnosis of HI/HA syndrome requires a thorough clinical evaluation, comprehensive biochemical analysis, and genetic testing. With the correct diagnosis, a patient with HI/HA syndrome can receive ongoing monitoring and care with the goal of preventing adverse neurologic sequelae